PRIORITY NEEDS FOR DEVELOPING STUDENT AFFAIRS MANAGEMENT OF RAYONGWITTAYAKOM SCHOOL BASED ON THE CONCEPT OF LIFE SKILLS - Sukcharoen, Chotika; Charoenkul, Nantarat (Journal of Educational Review Faculty of Education in MCU, 2026)
This research article aimed to: 1) study the current state and desired state of developing student affairs management of Rayongwittayakom School based on the concept of life skills; and 2) study the priority needs for developing student affairs management of Rayongwittayakom School based on the concept of life skills. This study employed a descriptive research design. The research instrument was a questionnaire validated for content validity with an Index of Item-Objective Congruence (IOC) of 0.50. The informants consisted of 5 school administrators and 155 teachers of Rayongwittayakom School, totally 160 participants. Statistics used for data analysis included frequency, percentage, arithmetic mean, standard deviation, Modified Priority Needs Index (PNImodified), and content analysis. The research findings revealed as follows 1) The current state of students' life skills at Rayongwittayakom School based on the concept of life skills was at a moderate level. Personal Abilities had the highest mean for the current state, while Cognitive Abilities had the lowest mean. The desired state of students' life skills at Rayongwittayakom School based on the concept of life skills was at the highest level, with Interpersonal Abilities having the highest mean and Cognitive Abilities having the lowest mean. The current state of student affairs management at Rayongwittayakom School based on the concept of life skills was at a high level, with Student Affairs Administration having the highest mean and the Student Care and Support System having the lowest mean. The desired state of student affairs management at Rayongwittayakom School based on the concept of life skills was at the highest level, with the Student Care and Support System having the highest mean and Discipline, Morality, and Ethics Promotion having the lowest mean. 2) The life skills dimension with the highest priority needs index was Interpersonal Abilities. The overall priority needs index for students' life skills at Rayongwittayakom School based on the concept of life skills was 0.338. When considering the scope of student affairs management development, the Student Care and Support System had the highest priority need for development.